BLOOD PRESSURE PHENOTYPES IN TREATED HYPERTENSIVE PATIENTS IN SUMMER AND WINTER: FOCUS ON MASKED UNCONTROLLED HYPERTENSION. PART 1: BLOOD PRESSURE PHENOTYPES PREVALENCE - M. I. Smirnova; V. M. Gorbunov; S. A. Boytsov; M. M. Loukianov; A. M. Kalinina; D. A. Volkov; A. D. Deev; Y. N. Koshelyaevskaya; E. N. Belova (Рациональная фармакотерапия в кардиологии, 2017)
Background. The seasonal variability of blood pressure (BP) and cardiovascular morbidity and mortality motivates researchers to search  for the new approaches of the antihypertensive treatment (AHT) efficacy assessment, including the analysis of interrelation between clinic and ambulatory BP, i.e. BP phenotypes.Aim. To evaluate the prevalence of BP phenotypes in treated hypertensive outpatients both in winter and summer.Material and methods. Hypertensive patients under regular AHT with available data of clinic BP and 24-hour BP monitoring both in winter and summer seasons (n=477) were selected from a outpatient database with clinic BP <160/100 mm Hg (n=1762). The BP threshold values from current guidelines were used for the BP phenotypes definition. The “controlled hypertension” phenotype was detected when  clinic and ambulatory BP levels were less than  threshold values, the “uncontrolled hypertension” – when  both levels exceeded the thresholds, the “white coat hypertension (WCH) in treated patients” – when  clinic BP was only increased, the “masked  uncontrolled hypertension” phenotype was ascertained if ambulatory BP was only elevated.Results. The study included 232 patients examined in Ivanovo (a relatively cold region; mean  age 53.5±9.3 years; 28% men; clinic BP 121.7±7.9 mm Hg; mean  duration of hypertension 4.6±6.3 years) and 245 patients from Saratov (a relatively hot region; mean  age 58.3±10.6 years; 56.3% men; clinic BP 127.5±14.9 mmHg; mean duration of hypertension 9.2±9.2 years; р<0.0001). In the Ivanovo cohort, ratio of BP phenotypes in summer and winter did not differ; the “masked  uncontrolled hypertension” phenotype prevailed (62.1% and 63.8% in winter and summer, respectively); AHT was effective in 27.6% and 29.7% of the patients in winter and summer, respectively. The prevalence of other phenotypes was low: uncontrolled hypertension – 9.5% in winter and 6.0% in summer; WCH in treated patients – less than  1%  in both seasons. The prevalence of BP phenotypes in the patients examined in Saratov differed in winter and summer (χ2=18.127, р<0.0001); the “masked  uncontrolled hypertension” phenotype rate was higher in summer than in winter (50.2% and 32.2%, respectively); the rates of other phenotypes were higher in winter: uncontrolled hypertension – 38.8% and 27.8%, controlled hypertension – 25.3% and 20.8%, WCH – 3.7% and 1.2% in winter and summer, respectively.Conclusion. We have found no seasonal changes in BP phenotypes prevalence in relatively younger hypertensive patients in a relatively cold region. The “masked  uncontrolled hypertension” phenotype was predominant (>60%) in this region. In contrast, the cohort  of relatively older patients with longer hypertension history examined in a relatively warmer region revealed significantly higher rate of masked uncontrolled hypertension in summer (50.2%) while prevalence of all other phenotypes – in winter.